Is frequent handling with reinforcement effective in improving management practices for feedlot heifers? - Vitor R. Pacor; Messy H. A. Pantoja; Douglas H. S. Almeida; Isabela M. D. Batista; Milena S. Consorti; Cihan Çamakçı; Cristiane G. Titto (Spanish Journal of Agricultural Research)
Aim of study: This study aimed to evaluate the effect of frequent handling of feedlot female cattle to decrease animal handling time and stress indicators.